Supporting adherence for people starting a new medication for a long-term condition through community pharmacies: a pragmatic randomised controlled trial of the New Medicine Service - Elliott, Rachel Ann; Boyd, Matthew J.; Salema, Nde-Eshimuni; Davies, James; Barber, Nicholas; Mehta, Rajnikant Laxmishanker; Tanajewski, Lukasz; Waring, Justin; Latif, Asam; Gkountouras, Georgios; Avery, A.J.; Chuter, Antony; et al. (BMJ Publishing Group, 2016)
Objective: To examine the effectiveness of the New Medicine Service (NMS), a national community pharmacy service to support medicines-taking in people starting a new medicine for a long-term condition, compared with normal practice.